2009
DOI: 10.1186/1471-2334-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte proliferation to mycobacterial antigens is detectable across a spectrum of HIV-associated tuberculosis

Abstract: BackgroundIdentifying novel TB diagnostics is a major public health priority. We explored the diagnostic characteristics of antimycobacterial lymphocyte proliferation assays (LPA) in HIV-infected subjects with latent or active TB.MethodsHIV-infected subjects with bacille Calmette Guérin (BCG) scars and CD4 counts ≥ 200 cells/mm3 entering a TB booster vaccine trial in Tanzania had baseline in vivo and in vitro immune tests performed: tuberculin skin tests (TST), LPA and five day assays of interferon gamma (IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(55 reference statements)
1
9
1
Order By: Relevance
“…Our study differs from previous cross-sectional studies in people with HIV that have shown greater frequency of IFN-γ responses in subjects with active or latent TB compared to subjects without active or latent TB [911, 38, 39]. These previous results might suggest that positive IFN-γ responses are always associated with an increased risk of TB disease in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study differs from previous cross-sectional studies in people with HIV that have shown greater frequency of IFN-γ responses in subjects with active or latent TB compared to subjects without active or latent TB [911, 38, 39]. These previous results might suggest that positive IFN-γ responses are always associated with an increased risk of TB disease in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…PPD or CFP-10 were increased in PTB and TSTþ HHC, compared to TSTÀ Non HHC, supporting that all of these responses differentiate these groups regardless of the stimuli used, and BCG vaccination. These findings are in agreement with immune response against PPD, CFP-10 or ESAT-6 determined by proliferation index [11,27], with IFN-g in cell culture supernatants [4,28], and with the percentages of IFN-g producing CD4 þ and CD8 þ lymphocytes where patients and latent infected individuals are differentiated from non-infected individuals [29,30], unlike the report by Cardoso et al in Brazil, who found that 8/10 TST-controls produced IFN-g in response to ESAT-6 [6].…”
Section: Discussionsupporting
confidence: 90%
“…However, we have shown in a previous study that in peripheral blood mononuclear cells, multiple antigens induce IFN-γ production [8], as well as that T cells from sarcoidosis BAL can produce an IFN-γ response to both mycobacterial ESAT-6 and KatG [14]. …”
Section: Introductionmentioning
confidence: 99%